Prevalence and phenotypic characterization of Enterococcus spp. isolated from food in Brazil - Camargo, Carlos Henrique [UNESP]; Bruder-nascimento, Ariane [UNESP]; Lee, Sarah Hwa In; Fernandes Júnior, Ary [UNESP]; Kaneno, Ramon [UNESP]; Rall, Vera Lúcia Mores [UNESP] (Sociedade Brasileira de Microbiologia, 2014)
We evaluated the frequency of enterococci from food and found 95.2% of positivity, being E. faecium and E. faecalis the most frequent species. High-level streptomycin resistance was observed, as well as gelatinase and hemolysis activity, showing the potential role of environmental strains as reservoir of virulence and resistance traits.
Keywords: Enterococcus spp.; food; antimicrobial resistance